Of Spaces and Ideas The Novels of Jim Crace and Simon Mawer - Chalupský, Petr (Karolinum, 2024)
This monograph provides a deeper insight into the work of two contemporary British novelists, Jim Crace and Simon Mawer, with a particular emphasis on their spatial sensibility as one of the defining elements of their poetics. Drawing on a range of literary-theoretical approaches to space, the study analyses selected novels by the two writers to demonstrate the ways in which they render space and place and, above all, the ways in which their spatial representations allow them to express the key ideas behind their stories, namely those of identity, history, and the relationship between an individual and the environment in which they live.
Keywords: Literární věda